Creating family time for working parents with preschool aged children - Pizarro, Ma. Cristine Madeleine J.; Ramirez, Maria Angelica B.; Jamero, Josephine Louise F. (Quezon City College of Home Economics, University of the Philippines Diliman, 2016)
This study aims to determine how Filipino working parents with pre-school aged children plan and organize their family time activities. Planning and organizing of 15 pairs of working parents were investigated through interviews which explored the management processes (planning, organizing, implementation, and evaluation). Data gathered from this exploratory study was analyzed by grouping common responses into themes. Results indicated that no fathers acted as planners and no mothers were final decision-makers when it came to creating family time. Furthermore, the children's interest and food availability in the venue were among the main considerations for family time. Parents perceived family time as opportunities for providing new learning experiences and establishing closeness with their children. Finally, the primary challenges encountered in family time activities include the work-family schedule conflict of the parents, and the behaviour of the children when spending time together.
Thesis (BS Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Work and family -- Philippines